Creating the constructivist classroom (Utah : Linton Professional Development Corporation, 1999)
Program 1: Constructivisim : student-centered active learning ; Program 2 : Getting started
volume 1. Elementary edition - volume 2. Middle school edition - volume 3. High school edition
Presenter: Bruce Marlowe and Marilyn Page
Keywords: Constructivism (Education); Active learning; Teaching